2017
DOI: 10.1111/codi.13434
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer resection in the Australian nonagenarian patient

Abstract: Surgical resection in the nonagenarian patient has an acceptable mortality and offers good overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Elective surgery mortality was 4.2%. These results are in accordance with other authors [8,10,12,22], who have reported mortality rates oscillating between 2.1% [8] and 23% [9].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Elective surgery mortality was 4.2%. These results are in accordance with other authors [8,10,12,22], who have reported mortality rates oscillating between 2.1% [8] and 23% [9].…”
Section: Discussionsupporting
confidence: 93%
“…Only five series have been reported in which nonagenarians with CRC have been exclusively included and most of them with a small number of patients [8][9][10][11][12]. Some other studies have differentiated the characteristics of nonagenarians but in the context of large series that mainly include octogenarians [2,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, similar subtypes are increasingly diagnosed in elderly patients . In the current study it is shown that the Australian nonagenarians indeed present with microsatellite instability and BRAF mutations, associated with these phenotypes. Whether the relatively high percentage of BRAF mutations in this patient group explains the poorer outcomes remains to be investigated.…”
mentioning
confidence: 53%
“…The International Society of Geriatric Oncology regularly issues guidelines about optimal treatment of these patients, since the consensus is that most of them are either overtreated or undertreated. In this issue of Colorectal Disease surgical treatment of an Australian cohort of nonagenarians is described . In fact, a number of similar studies has appeared in recent years .…”
mentioning
confidence: 95%
“…assessing 30‐day mortality and overall survival rates in nonagenarians with colorectal cancer. This retrospective study of 121 patients with median age 91 years concluded that surgical resection in the nonagenarian patient had acceptable 30‐day mortality (6.6%) and 1‐, 3‐ and 5‐year overall survival rates (82.6%, 50.2% and 32.3% respectively) .…”
mentioning
confidence: 99%